Aplikasi Android Pengenalan Klasifikasi Hewan Berdasarkan Jenis Makanan - Kristia Yuliawan; Alya Tasya Indriani; Arief Rahman Hakim (Lembaga Pengembangan Kinerja Dosen, 2025)
This research focuses on the development of an interactive educational Android application for animal classification based on their diet: herbivores, carnivores, and omnivores. The application leverages advances in deep learning and computer vision to analyze input images, distinguish morphological characteristics relevant to diet, and accurately identify and classify animal species. By adopting Agile methods, the project ensures flexibility in adapting to changing needs, enhances team collaboration, and enables iterative feature delivery with rapid feedback. The application is designed to engage users, particularly children and adolescents, through two main features: a